2021
DOI: 10.1177/1049731520984534
|View full text |Cite
|
Sign up to set email alerts
|

Role Stress, Burnout, and Workplace Support Among Newly Recruited Social Workers

Abstract: Purpose: This study examines the mediation and moderation roles of workplace support in the effect of role stress on burnout among newly recruited social workers in mainland China. Method: A total of 1,638 newly recruited social workers, those in their first year of professional employment, are invited as participants to complete a questionnaire package, which includes their demographic information, role stress, workplace support, and Maslach’s Burnout Inventory. Results: Role stress significantly correlates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
1
35
0
1
Order By: Relevance
“…Therefore, there have been enormous expansions to China’s social work academic programs within the last 40 years. From 1989 to 2018, social work undergraduate, master’s, and Ph.D. programs have risen from tens of annual graduating students to over 40,000 annual social work graduates ( Tang and Li, 2021 ). In tandem to rising social work academic institutions, the national Chinese social work labor force also drastically increased from 0.2 million in 2010, to 1.2 million in 2018 ( Li et al, 2012 ; Chan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there have been enormous expansions to China’s social work academic programs within the last 40 years. From 1989 to 2018, social work undergraduate, master’s, and Ph.D. programs have risen from tens of annual graduating students to over 40,000 annual social work graduates ( Tang and Li, 2021 ). In tandem to rising social work academic institutions, the national Chinese social work labor force also drastically increased from 0.2 million in 2010, to 1.2 million in 2018 ( Li et al, 2012 ; Chan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These statistics highlight just how quickly the field of social work has expanded throughout China, in a relatively short period of time. The future of social work in China, however, has become threatened by high burnout and turnover rates amongst social workers across the country ( Lin and Lan, 2014 ; Xu et al, 2016 ; Jiang et al, 2019 ; Su et al, 2020 ; Tang and Li, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job demands and resources has been found to be important factors of burnout and job satisfaction in social workers and other human service professionals (Demerouti et al, 2001;Tang et al, 2017;Su et al, 2020). In studies with samples of Chinese social workers, including both newly recruited social workers and early stage professionals (Tang et al, 2017;Tang and Li, 2021), scholars have found evidence of a positive relation between JD and burnout and turnover, as well as a negative relation between JR and burnout (Su et al, 2020;Luo and Lei, 2021). Su et al (2020), for example, applied the JD-R theory in an analysis of data from a nationally representative random sample of social workers (n = 5,800) and found that psychosocial resources, such as professional recognition and various types of social support, significantly reduced burnout.…”
Section: Jd-r and Burnoutmentioning
confidence: 99%
“…Within the past century, social work in China has experienced major periods of emergence, suspension, and revival (Tang and Li, 2021). In response to growing social issues that accompanied the country's rapid economic development since the 1980s, China has seen significant expansions to its social work labor force and education programs.…”
Section: Introduction Social Work Development In Chinamentioning
confidence: 99%